Penerapan Model Cooperative Tipe Scramble Dalam Materi Surat Al-kafirun Untuk Meningkatkan Sikap Toleransi Siswa Kelas V Pada Mata Pelajaran Al-Qur’an Hadits di MI KMI Tanjungsari - Siti Sopia; Gilang Maulana Jamaludin; Nuruddin Araniri (Al-Mau'izhoh, 2021)
This research is motivated by problems which show that the attitude of tolerance of students in class V MI KMI Tanjungsari is generally low, which can be seen when learning takes place marked by problems such as, if there is one student who does not agree, he will become the subject of ridicule for others, there are still students who are picky in helping each other and some students are still reluctant to be reprimanded if they are wrong and do not even accept being reminded. This research uses qualitative research with Classroom Action Research (CAR) design, where this research is used to investigate, find, describe, and explain data obtained from observations, interviews and documentation. This research uses qualitative research with Classroom Action Research (CAR) design, where this research is used to investigate, find, describe, and explain data obtained from observations, interviews and documentation. This research was carried out in three cycles and four stages, including: (1) planning, (2) implementation, (3) observation and (4) reflection. From the results of the research at the end of the cycle, namely cycle III, it was found that the results reached the target. Thus, the application of the scramble type cooperative model was able to increase students' tolerance attitude